Modeling the vulnerability of intelligence quotient as applied to educational strategic management - Eze, Foluke; Nu-Ue, Baridakara Livinus; Nkemka, Christopher Chukwuka (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
Intelligence quotient formulation is both mathematically and psychologically tractable. In this study, a mathematical model has been used to assess the vulnerability of intelligence quotient with application to educational strategic management. One research question guided the study and its findings are discussed in relation to educational strategic management. The analysis of the results obtained has revealed that as the modified mental age ranges from 3 years to 5 years, the IQ ranges from the estimated value of 15 to 25, when the modified mental age ranges from 6 years to 11 years, the IQ also ranges from the estimated value of 30 to 55, and as the modified mental age ranges from 12 years to 16 years, the IQ falls within the estimated value of 65 to 80. It is therefore our recommendation that the Federal Ministry of Education stipulated school age for various educational levels in Nigeria be enforced as follows: pre-nursery (3 months-2 years), nursery (3-5) years, primary (6 – 11) years, while 12 years upwards for post-primary.